2020
DOI: 10.1063/5.0004617
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric two-photon-absorption spectroscopy with three entangled photons

Abstract: We propose an interferometric pump-probe technique that employs three entangled photons generated by cascaded spontaneous parametric downconversion. A Mach–Zehnder interferometer made of two three-port waveguide arrays is inserted in the optical path. Two independent phases introduced to manipulate the entangled photon state serve as control parameters and can selectively excite matter pathways. Compared to two-photon-absorption of an entangled photon-pair, the three-photon signals are significantly enhanced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Furthermore, we demonstrated that the transmission measurement could provide the same information contents as in heterodyned four-wave mixing signals, such as 2D Fourier-transformed photon echo, although a simple optical system and simple light source are employed. This correspondence inspires us to anticipate that the usage of more elaborately engineered quantum states of light [46][47][48] would broaden the availability of quantum light spectroscopy [49] or molecular quantum metrology. The extensions of the present work in these directions are to be explored in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, we demonstrated that the transmission measurement could provide the same information contents as in heterodyned four-wave mixing signals, such as 2D Fourier-transformed photon echo, although a simple optical system and simple light source are employed. This correspondence inspires us to anticipate that the usage of more elaborately engineered quantum states of light [46][47][48] would broaden the availability of quantum light spectroscopy [49] or molecular quantum metrology. The extensions of the present work in these directions are to be explored in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…For simplicity, we consider the electric fields inside the one-dimensional nonlinear crystals. In the weak down-conversion regime, the state vector of the generated three photons is written as 65,71,75…”
Section: Theorymentioning
confidence: 99%
“…The momentum mismatch between the input and output photons in the n-th nonlinear crystal is expressed by ∆k n (ω, ω ′ ), and the length of the n-th crystal is given by L n . The momentum mismatches may be linearly approximated around the central frequencies of the generated beams, ωσ , as in 71,75 1. Schematic of frequency-dispersed two-photon coincidence counting measurement using entangled three photons generated via cascaded PDC pumped with a monochromatic laser of frequency ωp.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Such studies can also be extended to the domain of the characterization of unknown matter properties, where the non-classical correlation features of the optical modes induce controlled dynamical evolution of the matter modes, thereby emphasizing their scope as spectroscopic probes. [6][7][8][9][10] In such studies, the resultant spectral features of the matter modes crucially depend on the windowed dynamics in the joint time-frequency space, which were controllably induced. Depending on their generation processes, the photonic modes can be entangled in temporal-spectral, polarization, or the orbital angular momentum degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%